Prices, profit margins and intermediary market power: evidence from the matooke value chain in Uganda - Kuijpers, Rob; Smits, Esther; Steijn, Cedric; Mulumba, Nasser; Asindu, Marsy; Kruijssen, Froukje; Kikulwe, Enoch Mutebi (Emerald Publishing Limited, 2024)
There is widespread belief that intermediaries in African agri-food value chains have disproportionate market power. In this paper, the authors examine this belief by uncovering the purchasing and selling prices, costs and profit margins by farmers, intermediaries and retailers in the matooke (cooking banana) value chain in Uganda, and by analysing the prevailing value chain and market structures, seasonal entry and exit dynamics and the trading relationships in the chain.Data for this study were collected along the trading routes from the main matooke producing districts in South-West Uganda (Kabarole, Bunyangabo, Bushenyi, Isingiro and Mbarara) to the main urban markets around the capital Kampala. A structured survey was administered with 383 producers, 172 collectors and wholesalers and 71 retailers. In addition, key informant interviews and focus group discussions were held.The authors find that price mark-ups by intermediaries (selling prices minus purchasing prices) vary with the type of intermediary, season and location but generally reflect the costs of moving matooke down the value chain to the urban consumer. The authors do not find evidence for disproportionate market power among the intermediaries in the chain. Intermediaries enter and exit the market in peak and off-peak season, such that profits are kept in check. This seasonality does imply a small shift in market power in favour of farmers in off-peak season and in favour of intermediaries in the peak season.The investigation concentrated on an important and relatively homogenous staple crop along its main trade route. More remote areas, where there is less of an abundance of matooke, might still be characterised by local monopsonies where intermediaries have more market power due to high search and transport costs. Similarly, (local) monopsonies might exist for products for which there is a smaller market (segment), for products with a stronger seasonal variation in supply and for more perishable products.While there is an important literature on the role of intermediaries in African agri-food value chains, the evidence on intermediary market power is scant. Beliefs on intermediary market power are largely based on anecdotal evidence from farmers or inferred from observed prices or market structures. The paper contributes in addressing this important knowledge gap by studying the matooke value chain in Uganda.